Lives Not Worth Living Rethinking Autonomy and Assisted Dying in the Light of Profound Disability - Ripamonti, Lidia (2018)
Autonomy in dying, as in living, is often considered the mark of a free and self-affirming human being. However, this idea clashes with the daily reality of many severely disabled people who live in complete dependency but not without dignity, joyful relationships, and meaningful participation in the lives of others. The author looks at the phenomenon of an anticipated death from a philosophical perspective and argues against overstating the importance of autonomy: Exploring positive dynamics of encounter and relational care can help discover the unique significance of those who are most vulnerable in our society.
Keywords: Autonomy; assisted dying; disability models; profound disabilities; Relational Identity